2008
DOI: 10.1002/eji.200737809
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell regulation of epithelial TSLP expression plays an important role in the development of allergic rhinitis

Abstract: Epithelial cell-derived thymic stromal lymphopoietin (TSLP) is a master switch for asthma or atopic dermatitis by inducing a dendritic cell-mediated Th2-type allergic inflammation. Allergic rhinitis is also pathologically characterized by Th2-type allergic inflammation. This study demonstrates that mast cells regulate the epithelial TSLP expression in allergic rhinitis. TSLP expression was found to be up-regulated predominantly in the nasal epithelium in the ovalbumin (OVA)-sensitized and -nasally challenged m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 29 publications
4
83
0
Order By: Relevance
“…TSLP is expressed in the nasal mucosa of mice with AR (25) and is produced in activated mast cells (26). In our study, mice administered NJJ showed significantly decreased levels of TSLP in serum and nasal mucosal tissue ( Fig.…”
Section: Effects Of Njj On Il-32 Levelssupporting
confidence: 53%
“…TSLP is expressed in the nasal mucosa of mice with AR (25) and is produced in activated mast cells (26). In our study, mice administered NJJ showed significantly decreased levels of TSLP in serum and nasal mucosal tissue ( Fig.…”
Section: Effects Of Njj On Il-32 Levelssupporting
confidence: 53%
“…Indeed in line with our findings it was previously reported that induction of TSLP in airway epithelial cells is abolished in mice lacking MCs during allergic rhinitis. 31 MCs are able to produce a plethora of mediators upon their activation (reviewed in ref. 10).…”
Section: How Do Mast Cells Sense Gastrointestinal Helminthmentioning
confidence: 99%
“…For some experiments, rat anti-mouse TSLP neutralizing Ab (R&D Systems) or control rat IgG2a (15 mg/kg per mouse; Santa Cruz Biotechnology, Santa Cruz, CA, USA) were administered intraperitoneally 24 h before the first IL-13 challenge. The dosage of the Ab (15 mg/kg) was chosen based on previous experiments [30,31].…”
Section: Elisamentioning
confidence: 99%
“…The number of Hansel-positive eosinophils in the nasal mucosa or the number of PAS-positive goblet cells in the total nasal epithelial lining of the coronal sections was counted microscopically in a blinded manner and it was expressed as the number per total length of the total nasal epithelial lining of the coronal sections (the number/mm) as previously described [31]. Two or four specimens of the Hansel-or PAS-stained coronal sections from one mouse were selected.…”
Section: Quantification Of the Histological Examinationsmentioning
confidence: 99%